ON JULY 14, UNDER THE CHAIRMANSHIP OF THE PRESIDENT OF THE REPUBLIC OF UZBEKISTAN SHAVKAT MIRZIYOYEV, A VIDEO SELECTOR MEETING WAS HELD ON THE ISSUES OF INCREASING THE EMPLOYMENT OF YOUNG PEOPLE AND WOMEN, PROVIDING THEM WITH A SOURCE OF INCOME - Mengliyev Kahramon Kholiyorovich (Zeta Repository, 2023)
For half a year, the whole world has been living under heightened quarantine conditions. In this difficult period, the main problem in all countries is to support the needy sections of the population and provide them with income. 732,000 of the unemployed in Uzbekistan are young people, 834,000 are women. In order to effectively solve the problems of youth, on June 30 of this year, the Presidential Decree "On measures to fundamentally reform and bring the youth policy to a new level in the Republic of Uzbekistan" was adopted. In accordance with this decree, the Youth Affairs Agency was established, which has the necessary authority and financial resources to submit issues to state agencies in conducting youth policy.